Forensic Research of Phaleristic Items for Their Estimation - A. Ya. Asnis; G. G. Bocharov; A. A. Selivanov; S. N. Khaziev (Теория и практика судебной экспертизы, 2020)
Collecting phaleristics is quite a common hobby in all countries. The cost of awards, medals, and other items of phaleristics is determined by their rarity, condition, manufacturing complexity, presence of precious metals and stones.Forensic research of phaleristics for estimation differs from their appraisal by collectors themselves, appraisers of antique trade organizations, pawnshops, and auctioneers in the legal significance of the costing for interested parties. It is conducted according to the methodology of forensic commodity research to determine the market value of objects of various product groups; besides, there is a need to establish authenticity for certain types of products.The article presents an algorithm for forensic appraisal of phaleristic objects. It is shown that state awards of the USSR, RSFSR, and the Russian Federation do not have market cost according to the current Russian legislation as they are removed from the civil circulation. For these items, only the cost of the precious metals used in their production can be established. This cost is determined according to the methodology approved by the Russian Ministry of Finance.